PROGRAM PENGASUHAN POSITIF UNTUK MENINGKATKAN KUALITAS PENGASUHAN IBU - , Sisca Efnita; , Prof. Dr. Sartini Nuryoto, Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Positive parenting for preschool can prevent and reduce misbehavior children, and support academic competence formal school children. But, the common parent applied a negative parenting because they less knowledge, less competence and not to understand the parenting. This research to aim at to know influence positive parenting program that was inspired with triple P to increase quality mother care preschool children (3-5 years old). The participant in this study contained of mother who has preschool child in Yogyakarta (n=10). The participant was divided into two, group experiment with program positive parenting (5 persons) and group control (5 persons). The quasi experiment method untreated control group design with pretest and posttest was designed to this study. The result of this study showed that positive parenting program canât improve parenting quality of mother who has preschool children.